New Dendrobranchiata fossil preserved in the Brazilian Cretaceous (Aptian/Albian) from the Araripe Basin, Piauí State - Barros, Olga Alcântara; Oliveira, Paulo Victor De (Zootaxa, 2023)
The fossil shrimp Somalis piauiensis n. gen. n. sp. is a new fossil record of Penaeoidea from the Araripe Basin. The purpose of this study is to describe a new decapod crustacean from the Romualdo Formation of the Santana Group and compare it with other fossil Dendrobranchiata described from this basin. The new fossil is characterized by a carapace with antennal and branchiostegal spines. Long rostrum, with thirteen evident dorsal spines yielding a serrate appearance. The laminar scaphocerite is large with a weakly rounded lateral margin and is longer than the rostrum. The fossil specimen is the first occurrence of shrimp in the Piauí territory.